Multi-stage actuation systems and control - Du, Chunling; Pang, Chee Khiang (Boca Raton, FL : CRC Press, 2019)
"This book is designed for academic researchers and engineering practitioners in systems and control, especially those engaged in the area of control in mechanical systems with microactuators and multi-stage actuations. The book aims at empowering readers with a clear understanding of multi-stage mechanism, different microactuators' performances, their limitations to control system performance and problems encountered in control system design and techniques for solving these problems and dealing with these limitations. Special attention is given to recently developed control techniques in three-stage systems and MEMS positioning stage. Real-world examples are given to demonstrate the control techniques such as dual-stage and three-stage systems in hard disk drives and micro XY stage in manufacturing systems"--
OCLC-licensed vendor bibliographic record.
Keywords: Microactuators; Automatic control; TECHNOLOGY & ENGINEERING -- Engineering (General)